PERAN DIPLOMASI PERTAHANAN INDONESIA DALAM KERJASAMA PERTAHANAN INDONESIA DAN AMERIKA SERIKAT - Beni Sukadis (Mandala: Jurnal Ilmu Hubungan Internasional, 2018)
This research is focused on Indonesia-US diplomatic relations in politics and defense. The relationships are very volatile both in terms of closeness and depth of defense cooperation between the two countries. Bilateral defense cooperation is aimed at improving military relations between the two countries and building professionalism of the TNI - in addition to achieving the Indonesian defense goals such as maintaining the sovereignty and integrity of the country. Indonesia has interest in maintaining defense cooperation with the US due to the fact that the majority of Indonesia’s major defense equipment is from the US and other western countries. By taking the perspective of the Susilo B. Yudhoyono administration (2004-2014), defense diplomacy is closely related to the Minimum Essential Force (MEF) program. The MEF program has initiated the Indonesian government to cooperate with the US in the context of maintenance and procurement of weapons that have been embargoed since 1999. This research also finds that among various defense cooperation activities between Indonesia and the US, the major one is actually in the field of education and training, e.g., short courses, staff and command education, seminars, post graduate programs and others. Meanwhile, the other defense cooperation activity, namely defense industry, is still very minor until today. The method of research is qualitative using descriptive analytical collected from the interview of practitioners and from secondary sources such  book, paper, and open sources